Health effects of a ban on late-night alcohol sales - Matthias Bäuml; Jan Marcus; Thomas Siedler (Health Economics, 2022)
This paper studies the impact of a ban on late-night off-premise alcohol sales between 10 p.m. and 5 a.m. in Germany. We use three large administrative data sets: (i) German diagnosis related groups-Statistik, (ii) data from a large social health insurance, and (iii) Road Traffic Accident Statistics. Applying difference-in-differences and synthetic-control-group methods, we find that the ban had no effects on alcohol-related road casualties, but significantly reduced alcohol-related hospitalizations (doctor visits) among young people by around 9 (18) percent. The decrease is driven by fewer hospitalizations due to acute alcohol intoxication during the night—when the ban is in place—but not during the day.
Keywords: 330; alcohol control policies; binge drinking; difference-in-differences; road casualties; sales restrictions; synthetic control